Different Endomembrane Trafficking Pathways Establish Apical and Basal Polarities. Issue 1 (23rd December 2016) - Li, Ruixi; Rodriguez-Furlan, Cecilia; Wang, Junqi; van de Ven, Wilhelmina; Gao, Ting; Raikhel, Natasha V.; Hicks, Glenn R.
Abstract : The inhibitor endosin 16 defines a distinct pathway for endomembrane sorting via regulation of the small GTPase RabA that is essential for the establishment of cell polarity. Abstract: The endomembrane system is an interconnected network required to establish signal transduction, cell polarity, and cell shape in response to developmental or environmental stimuli. In the model plant Arabidopsis thaliana, there are numerous markers to visualize polarly localized plasma membrane proteins utilizing endomembrane trafficking. Previous studies have shown that the large ARF-GEF GNOM plays a key role in the establishment of basal (rootward) polarity, whereas the apically (shootward) polarized membrane proteins undergo sorting via different routes. However, the mechanism that maintains apical polarity is largely unknown. Here, we used a chemical genomic approach and identified the compound endosidin 16 (ES16), which perturbed apically localized plasma membrane proteins without affecting basal polarity. We demonstrated that ES16 is an inhibitor for recycling of apical, lateral, and nonpolar plasma membrane proteins as well as biosynthetic secretion, leaving the basal proteins as the only exceptions not subject to ES16 inhibition. Further evidence from pharmaceutical and genetic data revealed that ES16 effects are mediated through the regulation of small GTPase RabA proteins and that RabA GTPases work in concert with the BIG clade ARF-GEF to modulate the nonbasal trafficking. Our results reveal that ES16 defines a distinct pathway for endomembrane sorting routes and is essential for the establishment of cell polarity.